Code Mixing in Female Teenagers’ Daily Conversation at An English Dormitory - Alalloh, Roisatul Muttaqin (Language Horizon: Journal of Language Studies, 2023)
The phenomenon of code-mixing is a common occurrence, particularly among multilingual people. Code mixing refers to combining two or more languages in which lexical and grammatical elements from multiple languages occur in a single sentence. This study deals with code-mixing in the females' English dormitory at the Islamic boarding school Al-yasini Pasuruan. The objectives of this study are to classify the types of code-mixing used, and reveal the factors that cause them to do code mixing. This study used qualitative method for collecting and processing the data, while in the form of words, phrases, and sentences became the data of the study. Musyken’s theory supports research question 1, and Hudson’s theory supports research question 2. This study employed a combination of questionnaires, observations, and interview techniques. There were 3 processed was done in the data analysis, such as (1) collecting the data from the questionnaires and non-participatory observation in the form of voice records (2) Classifying the data into the provided categories of options, and (3) Revealing the data from the classification results and supported by the interview data. The study revealed that there were 124 informants who lived in English dormitory as members, 48 informants for less than one year (more than six months), 52 informants for more x than one year, and 24 informants for more than three years. The data shows that the three groups of informants used three types of code mixing, such as insertion, alternation approach, and congruent lexicalization type. Individual and social factors cause code-mixing, and no cultural factor exists.